2017
DOI: 10.1111/obr.12607
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing in obesity: a systematic review and exploratory meta‐analysis

Abstract: SummaryThe role of emotional functioning in the development and maintenance of obesity has been investigated, but the literature is poorly integrated. A systematic review and meta-analysis was performed to explore emotional processing impairments in obesity. PubMed, Web of Knowledge and PsycINFO databases were searched in March 2016, yielding 31 studies comparing emotional processing competencies in individuals with obesity, with or without binge eating disorder (BED), and control groups. Meta-analyses demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 66 publications
(107 reference statements)
3
52
0
5
Order By: Relevance
“…[4][5][6] Although the emotional etiology of obesity is still unclear, several rooted negative psychological aspects have been observed. 7 Children and adolescents with overweight or obesity presented higher levels of depression, 8 lower levels of self-efficacy, self-esteem, and higher body dissatisfaction than children and adolescents with normal weight. [9][10][11] In this sense, the practice of physical exercise may reduce these deleterious effects associated with overweight or obesity in adolescence.…”
Section: Introductionmentioning
confidence: 96%
“…[4][5][6] Although the emotional etiology of obesity is still unclear, several rooted negative psychological aspects have been observed. 7 Children and adolescents with overweight or obesity presented higher levels of depression, 8 lower levels of self-efficacy, self-esteem, and higher body dissatisfaction than children and adolescents with normal weight. [9][10][11] In this sense, the practice of physical exercise may reduce these deleterious effects associated with overweight or obesity in adolescence.…”
Section: Introductionmentioning
confidence: 96%
“…In obesity research, alexithymia is reported to be significantly more frequent among obese patients compared with controls without obesity (Da Ros, Vinai, Gentile, Forza, & Cardetti, ; Fernandes, Ferreira‐Santos, Miller, & Torres, ; Kirsten & Ridout, , p. 158). In a recent cross‐sectional study, alexithymia, particularly the DIF factor, was associated with abdominal obesity in patients with type 1 diabetes (Melin et al, ) and predicted failure of a cognitive behavioural therapy group intervention for overweight and obese patients (Sawamoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups, on the contrary, are more cautious about the FA concept arguing that there is not enough evidence so far to assure its diagnostic entity, and that some of the findings obtained in preclinical research, associated with the addictive capacity of certain palatable foods, have not yet been completely replicated in humans (Albayrak, Wölfle, & Hebebrand, ; Hebebrand et al, ). They will appeal more to the neurobiological vulnerability of certain people and their greater susceptibility to using food, as a means of coping with problems and negative affect (Fernandes, Ferreira‐Santos, Miller, & Torres, ; Davis & Loxton, ; Wolz et al, ; Granero et al, ; Leslie, Turton, Burgess, Nazar, & Treasure, ; Treasure et al, ), than to the addictive components of the food. One argument is that “food addiction” is incorrect as it may be the act of eating rather than the substance itself (the food) which is addictive and the term “eating addiction” may be more appropriate (Hebebrand et al, ), In this regard, some groups are interested in the parallels between the FA construct and behavioral addictions, where “substance” is not per se crucial, but the behavior itself (in that case gambling, gaming, or buying) (Jiménez‐Murcia et al, ; Granero et al, ).…”
mentioning
confidence: 97%